Challenges and Opportunities in Vermont - Allbee, Roger (Cuizine, 2010)
In this short essay, the author explores the importance of terroir, or the taste of place, for the future of food and agriculture in Vermont. Here, the taste of place is connected to increased engagement with local foods. However, Allbee claims that local can also mean foods that reflect a unique local character, that tell the story of a place, bringing the tastes, history, and culture of a region to the consumer.